Salivary cortisol as a peripheral biomarker of stress in surgical patients: Salivary cortisol in surgical patients - Vicković, Sanja; Zdravković, Ranko; Maričić Prijić, Sanja; Nikolić, Dragan; Pap, Dragana; Čolak, Emina; Jovičić, Snežana (Journal of Medical Biochemistry, 2023)
Background: Surgical stress and pain result in activation of hypothalamus-pituitary-adrenal axis. The aim of this study was to establish the effects of postoperative pain and various modalities of analgesic administration on salivary and serum cortisol levels, as well as to establish the validity of salivary cortisol as a stress indicator in surgical patients. Methods: A randomized controlled trial involving 60 patients scheduled for elective abdominal aortic aneurysm surgery. Patients were randomly divided into two groups depending on the model of postoperative analgesia. The first group (MI) included patients given morphine doses 0.1mg/kg/6h s.c. intermittently. The second group (MPCA) included patients who received morphine via the PCA system - intravenous administration of morphine adjusted to a dose of 1mg per shot and a lockout interval of 6 minutes. Results: The intensity of pain did not significantly vary until the hour 10 post-surgery. However, in the period from hour 10 to hour 18 post-surgery, higher intensity of pain was reported in group MPCA (P < 0.05). Hemodynamic instability was more prevalent in the MI group (40.0% vs 6.7%, P = 0.0048). Serum cortisol levels were almost identical in both groups (MI 509.4 vs MPCA 511.0nmol/L, P = 0.1473). Higher values of salivary cortisol were recorded in group MPCA; however, the difference was not statistically significant (47.1 vs 116.3nmol/L, P = 0.0970). Conclusions: Our study confirmed that salivary cortisol is a more sensitive stress biomarker in surgical patients as compared to blood cortisol.